Hepatoid adenocarcinoma in ureter with next-generation sequencing: A case report and literature review - Mengxin Lu; Yueying Li; Dongliang Hu; Jingtian Yu; Hang Zheng; Tongzu Liu (BMC, 2024)
Abstract Background Hepatoid adenocarcinoma (HAC) is rare in the urinary system, with only 7 reported cases in upper urinary tract. This report aimed to explore the genetic characteristics of ureteral HAC for first time, and to describe the treatment prognosis of ureteral HAC. Case presentation We present a rare case of ureteral HAC in a 53-year-old female, showing elevated serum levels of AFP and CEA, prolonged chronic irritation may be an important cause of her ureteral HAC. Radical nephroureterectomy was performed, the serum levels of AFP and CEA decreased significantly, and metastasis in lymph nodes was found at 9 months after surgery, she had no related symptoms after 18 months postoperatively without adjuvant chemotherapy. Three driver somatic mutations in cancer were identified by NGS testing, including: TP53D281H, KMT2DL1211Ifs*2, KMT2DT1843Nfs*5, demonstrating that ureteral HAC has the similar mutational features to upper tract urothelial carcinoma. Homologous-recombination deficiency (HRD) was positive in this tumor with no mutations in HRD-related genes, which was possibly induced by the copy number deletion of SETD2 gene. Conclusions We report a rare case of ureteral HAC with elevated serum levels of AFP and CEA. NGS testing demonstrated that ureteral HAC has the similar mutational features to upper tract urothelial carcinoma, which is an important guide for the diagnosis and treatment of ureteral HAC.